El Fondo Renée Lamberet conservado en el Institut Français d’Histoire Sociale de París - Gérard Brey (Cahiers de Civilisation Espagnole Contemporaine)
Evocation of the militant for Spanish anarchism and historian Renée Lamberet (1901-1980) and of the documentation she bequeathed to the Institut Français d'Histoire Sociale of Paris.